1994
DOI: 10.1046/j.1537-2995.1994.34694295060.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival after blood transfusion

Abstract: Receipt of a blood transfusion can be used as a descriptive epidemiologic index of morbidity in the general population, as it is independently predictive of mortality, adding to the predictive value of age, gender, and previous hospitalization. There is a dose-response relationship between the amount of blood components received and a reduction in the subsequent length of survival. However, when a county's entire population is studied, posttransfusion mortality due to underlying disease is substantially lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
98
3
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 17 publications
13
98
3
2
Order By: Relevance
“…[9,10]. Furthermore, Vamvakas and Taswell quantified the association between blood transfusion and mortality in a more broadly based U.S. population, and found a dose-response relationship between the number of blood transfusions and a subsequent shorter length of survival (Table 2) [11]. Concern has also been expressed about the quality of stored blood and observations of negative outcomes in transfused patients.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10]. Furthermore, Vamvakas and Taswell quantified the association between blood transfusion and mortality in a more broadly based U.S. population, and found a dose-response relationship between the number of blood transfusions and a subsequent shorter length of survival (Table 2) [11]. Concern has also been expressed about the quality of stored blood and observations of negative outcomes in transfused patients.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that patients with colon cancer who received a blood transfusion had twice the infection rate of those who were not transfused (12% vs 25%). 26 Patients who receive blood transfusions have one-and ten-year mortality rates of 24% and 52 % respectively. 27 Irrespective of these risks, most patients would prefer not to receive blood if at all possible for many reasons, and in view of the uncertainty about the short-and long-term effects of blood transfusion, we should make every effort to avoid this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Carless i saradnici su 2010. godine analizirali 75 studija koje ispituju efikasnost intraoperativnog spašavanja krvi i to u ortopediji (36 studija), kardiohirurgiji (33 studije) i vaskularnim procedurama (6 studija) i doneli zaključak da se njegovom upotrebom smanjuje potreba za transfuzijom donorske krvi, kao i to da ne izaziva nastanak ikakvih neželjenih događaja 10 . Pored definisanih neželjenih efekata alogene krvi, postoje i oni nedefinisani koji se odnose na dugoročne efekte transfuzije alogene krvi na mortalitet i morbiditet 11,12,13 . Ispitivano je dugoročno preži-vljavanje 1915 bolesnika koji su imali neku kardiohirušku intervenciju, gde je 649 bolesnika primilo alogenu transfuziju i došlo se do zaključka da je taj broj bolesnika imao kraće preživljavanje za 5 godina u proseku u odnosu na one koji nisu primali donorsku krv 14 .…”
Section: Diskusijaunclassified